Motivasi Belajar Mahasiswa PendidikanakuntansiPada Mata Kuliah Filsafat PendidikanDalam Perspektiflingkungan Belajar Dan InteraksiTeman Sejawat Tahun Ajaran 2016/2017 - Prahastiwi, Mydia Inggit; , Drs. Sami'an, M.M (2017)
ABSTRACT The research aims are to know: 1) The influence of the learning environment on learning motivation of students in philosophy of education subject, 2) The effect of peer interaction on learning motivation of students in philosophy of education subject, 3) Environmental influences learning and peer interaction on learning motivation of students in philosophy of education subject. This is a quantitative research and a survey design. The population in this study were all of the accounting education students in University Muhammadiyah of Surakarta periode 2016 that count 341 number, 181 students as sample that taken by technique proportional non random sampling with insidental sampling. Data collection instrument with questionnaire methode which qulified by validity and realibity test. The technique of analysis data used is anlysis of multiple regression, t-test, f-test, effective contribution and relative contribution. Based on the result of regression analysis which obtained from the equation regression in this research, that is: Y = 17,342 + 0,291X1 + 0,156X2. The conclusion that gained from these equation are: 1) there is significant influence between learning environment towards learning motivation of students on philosophy of education subject based on T test gained thitung>ttabel that is 30,679 > 1,984 and the significant value < 0,05 which is 0,000. 2) There is significant influence between peers interaction towards learning motivation of students on philosophy of education subject based on T test gained thitung>ttabel that is 2,882 > 1,984 and the significant value < 0,05 which is 0,001. 3) There is significant influence between learning environment and peers interaction towards learning motivation of students on philosophy of education based on F test gained Fhitung>Ftabel that is 27,137 > 3,05 with significant value 5%. The result calculation of the R2 value gained 23,4% the learning motivation of students on philosophy of education subject influence by learning environment and peers interaction, and the 76,6% influence by another variable that not examined in this research. Keywords: Learning environment; Learning motivation; Peers Interaction.